(untitled) (Sains Humanika, 2017)
In the teaching of literature in secondary school, some teachers prefer the traditional method and this causes students to view literature as a boring subject. In this technological era, technology method such as digital stories have been a powerful tool in teaching and learning that engages both teachers and their students (Robin, 2008). This study investigates the use of digital stories in the teaching and learning of poems in an upper form classroom in Malaysia. In a mixed method study of eleven participants , multiple data were collected through pre-test and post-test, observations, and interviews. The results showed that using digital stories could increase students’ understanding, participation and interest in learning the poems as well as promote students’ ability in meaning making by involving them in fun and meaningful activities in the classroom. Students were also able to engage themselves in gathering information as well as giving personal response. The findings of the study encourage the teachers to integrate technology in the teaching and learning of literature component especially in the Malaysian secondary school context.